Nanoscale Devices for Rectification of High Frequency Radiation from the Infrared through the Visible: A New Approach. (29th April 2012) - Miskovsky, N. M.; Cutler, P. H.; Mayer, A.; Weiss, B. L.; Willis, Brian; Sullivan, T. E.; Lerner, P. B.
Abstract : We present a new and viable method for optical rectification. This approach has been demonstrated both theoretically and experimentally and is the basis fot the development of devices to rectify radiation through the visible. This technique for rectification is based not on conventional material or temperature asymmetry as used in MIM (metal/insulator/metal) or Schottky diodes, but on a purely sharp geometric property of the antenna. This sharp "tip" or edge with a collector anode constitutes a tunnel junction. In these devices the rectenna (consisting of the antenna and the tunnel junction) acts as the absorber of the incident radiation and the rectifier. Using current nanofabrication techniques and the selective atomic layer deposition (ALD) process, junctions of 1 nm can be fabricated, which allow for rectification of frequencies up to the blue portion of the spectrum. To assess the viability of our approach, we review the development of nanoantenna structures and tunnel junctions capable of operating in the visible region. In addition, we review the detailed process of rectification and present methodologies for analysis of diode data. Finally, we present operational designs for an optical rectenna and its fabrication and discuss outstanding problems and future work.